AN ANALYSIS OF FIGURATIVE LANGUAGE USED IN THE LYRIC OF “A WHOLE NEW WORLD” BY ZAYN MALIK AND ZHAVIA WARD - Siti Nursolihat; Evie Kareviati (IKIP Siliwangi, 2020)
Language is a tool of communication used by people anywhere and every time. Now days people commonly find a figurative language in daily life, for example in a lyric of song. Figurative language is a way to express an idea in implicit way. This research is trying to analyze the figurative languages which exist in the lyric of song “A Whole New World” and trying to find out its meaning by analyzing its contextual meaning. This is a descriptive qualitative research. The data instrument is the song lyric which taken from Genius website. The result showed that this song consist of some figurative languages, such as alliteration, simile, personification, metaphor, and hyperbole. Furthermore, the most figurative language used in the lyric is metaphor. It is highly relatable with the imaginative theme of the song itself. The contextual meaning of each figurative language is also explained based on the situation of the lyric.